Chronic Grief Management for Dementia Caregivers in Transition: Intervention Development and Implementation - Paun, Olimpia (2011)
Research reveals that Alzheimer’s disease (AD) caregivers (CGs) do not relinquish their role after placing a family member in long-term care. Caregivers report increased emotional upset around the time of placement, with sustained losses over time leading to chronic grief. Chronic grief increases caregivers’ risk for depression and suicide. There are no documented interventions designed to decrease CGs chronic grief post placement. The Chronic Grief Management Intervention (CGMI) builds on existing evidence to target caregiver chronic grief in the transition of a family member into long-term care. The intervention is structured into three major components: 1) knowledge, 2) skill in communication and conflict resolution, and 3) chronic grief mangement skill. The 12-week intervention was pilot tested with thirty four caregivers for feasibility and preliminary effects on caregiver skill, knowledge, chronic grief, and depression. This article presents a general study description while focusing on the development and implementation of the CGMI.